13C labelled cholesteryl octanoate breath test for assessing pancreatic exocrine insufficiency. Issue 1 (1st January 1998) - Ventrucci, M; Cipolla, A; Ubalducci, G M; Roda, A; Roda, E
Abstract : Background —A non-invasive test for assessment of fat digestion has been developed based on the intraluminal hydrolysis of cholesteryl-[1- 13 C]octanoate by pancreatic esterase. Aims —To determine the diagnostic performance of this breath test in the assessment of exocrine pancreatic function. Methods —The test was performed in 20 healthy controls, 22 patients with chronic pancreatic disease (CPD), four with biliopancreatic diversion (BPD), and 32 with non-pancreatic digestive diseases (NPD); results were compared with those of other tubeless tests (faecal chymotrypsin and fluorescein dilaurate test). Results —Hourly recoveries of 13 CO2 were significantly lower in CPD when compared with healthy controls or NPD. In patients with CPD with mild to moderate insufficiency, the curve of 13 CO2 recovery was similar to that of healthy controls, while in those with severe insufficiency it was flat. In three patients with CPD with severe steatorrhoea, a repeat test after pancreatic enzyme supplementation showed a significant rise in 13 CO2 recovery. The four BPD patients had low and delayed 13 CO2 recovery. Only eight of the 32 patients with NPD had abnormal breath test results. There was a significant correlation between the results of the breath test and those of faecal chymotrypsin, the fluorescein dilaurate test, and faecal fat measurements. For the diagnosis of pancreatic disease using the three hour cumulative 13 CO2 recovery test, the sensitivity was 68.2% and specificity 75.0%; values were similar to those of the other two tubeless pancreatic function tests. In seven healthy controls, nine patients with CPD, and nine with NPD a second breath test was performed using Na-[1- 13 C]octanoate and a pancreatic function index was calculated as the ratio of 13 C recovery obtained in the two tests: at three hours this index was abnormal in eight patients with CPD and in three with NPD. Conclusion —The cholesteryl-[1- 13 C]octanoate breath test can be useful for the diagnosis of fat malabsorption and exocrine pancreatic insufficiency.